2019
DOI: 10.1371/journal.pcbi.1007562
|View full text |Cite
|
Sign up to set email alerts
|

Systems-level analysis of NalD mutation, a recurrent driver of rapid drug resistance in acute Pseudomonas aeruginosa infection

Abstract: Pseudomonas aeruginosa, a main cause of human infection, can gain resistance to the antibiotic aztreonam through a mutation in NalD, a transcriptional repressor of cellular efflux. Here we combine computational analysis of clinical isolates, transcriptomics, metabolic modeling and experimental validation to find a strong association between NalD mutations and resistance to aztreonam-as well as resistance to other antibiotics-across P. aeruginosa isolated from different patients. A detailed analysis of one pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…6 ). This risk may be specific to transplant recipients damaged by conditioning regimen with injury to the intestinal barrier that could facilitate the translocation of pathogens from the gut into the blood 40 . Still, allo-HCT patients provide a unique opportunity to study microbiota dynamics in such extreme situations.…”
Section: Technical Validationmentioning
confidence: 99%
“…6 ). This risk may be specific to transplant recipients damaged by conditioning regimen with injury to the intestinal barrier that could facilitate the translocation of pathogens from the gut into the blood 40 . Still, allo-HCT patients provide a unique opportunity to study microbiota dynamics in such extreme situations.…”
Section: Technical Validationmentioning
confidence: 99%
“…Using a crystal violet assay, we confirmed that the depletion of known regulators such as AmrZ, FleQ or PA0191 significantly affected biofilm formation (Figure 2-figure supplement 4B). Similar to other prokaryotic TFs, both activating or repressing phenotypes could be observed upon manipulating TF binding in P. aeruginosa (73,(84)(85)(86)(87)(88)(89)(90)(91). However, we observed that most mutant strains did not show an overt biofilm-associated phenotype, even those of some previously known positive TFs such as RsaL (92), CprR (46), AlgB (76,93), CdpR (75), BqsR (Synonym: CarR) (71, 72) and PA3782 (63).…”
Section: Pa0225 Is a Novel Regulator Of Biofilm Productionmentioning
confidence: 58%
“…Using a crystal violet assay, we confirmed that the depletion of known regulators such as AmrZ, FleQ, or PA0191 significantly affected biofilm formation ( Figure 2—figure supplement 4B ). Similar to other prokaryotic TFs, both activating and repressing phenotypes could be observed upon manipulating TF binding in P. aeruginosa ( Yang et al, 2019 ; Poole et al, 1996 ; Kawalek et al, 2019 ; Ha et al, 2004 ; Wu and Jin, 2005 ; Jin et al, 2011 ; Daddaoua et al, 2017 ; Chugani et al, 2001 ; Yan et al, 2019 ). However, we observed that most mutant strains did not show an overt biofilm-associated phenotype, even some of those previously known biofilm-regulatory TFs such as RsaL ( Rampioni et al, 2009 ), CprR ( Badal et al, 2020 ), AlgB ( Chand et al, 2012 ; Mukherjee et al, 2019 ), CdpR ( Zhao et al, 2016 ), BqsR (Synonym: CarR) ( Guragain et al, 2016 ; Sarkisova et al, 2005 ), and PA3782 ( Finelli et al, 2003 ).…”
Section: Resultsmentioning
confidence: 79%
“…For instance, mutations in genes encoding regulators of MDR efflux pumps can lead to the overexpression of the latter and, as a consequence, a more efficient extrusion of drugs. In the case of mexAB-oprM, overexpression may be due to mutations in the gene that encodes its local repressor, MexR, or in genes encoding other secondary regulators, NalC or NalD, events that have been reported in vivo [ 63 , 64 ]. Similarly, mexCD-oprJ and mexXY-oprM overexpression could be driven by spontaneous mutations in genes encoding their repressors, NfxB and MexZ, respectively [ 63 , 65 ].…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%